(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Musculoskeletal (MSK) disorders are frequently observed in patients with chronic kidney disease (CKD), particularly those undergoing dialysis. Dialysis, which purifies blood when kidney function declines, can lead to electrolyte imbalances and increased protein and uric acid levels, resulting in muscle deterioration and regional MSK issues. Objective: To assess the frequency of MSK disorders among dialysis patients with CKD at the Institute of Kidney Diseases, Hayatabad, Peshawar. Methods: A descriptive cross-sectional study was conducted from March to October 2022, involving 100 dialysis patients (47 males, 53 females) selected through convenience sampling. Patients with rheumatic disorders, limb amputations, joint restrictions due to skin lesions or contractures, or those unwilling to participate were excluded. The Nordic Musculoskeletal Questionnaire was used for data collection. Results: Pain in the last 12 months was most commonly reported in the knee (53%), followed by the shoulder and lower back (46%), ankle (36%), and neck (30%). Activity limitation was highest in the knee (48%) and shoulder/lower back (38%). Pain in the last 7 days was also most frequent in the knee (38%). Conclusion: MSK disorders are highly prevalent among dialysis patients, with the knee being the most commonly affected area. Female patients showed slightly higher prevalence.